Antimicrobial use in hospitalized patients: a multicentre point prevalence survey across seven hospitals in Ghana. Issue 3 (12th July 2021) - Labi, Appiah-Korang; Obeng-Nkrumah, Noah; Dayie, Nicholas T K D; Egyir, Beverly; Sampane-Donkor, Eric; Newman, Mercy Jemima; Opintan, Japheth Awuletey
Abstract: Background: Antimicrobial resistance (AMR) is a public health crisis of global proportions. Data is required to understand the local drivers of antimicrobial resistance and support decision-making processes including implementation of appropriate antimicrobial stewardship strategies. Objectives: To measure antimicrobial usage in hospitals in Ghana. Methods: Using the Global Point Prevalence instruments and processes, we conducted point prevalence surveys across AMR surveillance sentinel hospitals in Ghana, between September and December 2019. Hospital records of all inpatients on admission at 0800 hours on a specific day were reviewed for antimicrobial use at the time of the survey. Data on antibiotic use, including indication for use and quality of prescribing were recorded. Results: Overall prevalence of antibiotic use across the sentinel sites was 54.9% ( n =  1591/2897), ranging between 48.4% ( n =  266/550) and 67.2% ( n =  82/122). The highest prevalence of antibiotic use 89.3% ( n =  25/28) was observed in adult ICUs. The average number of antibiotics prescribed per patient was 1.7 ( n =  1562/2620), with the majority (66%, n =  728/2620) administered via the parenteral route. The five most-commonly used antibiotics were metronidazole (20.6%, n =  541/2620), cefuroxime (12.9%, n =  338/2620), ceftriaxone (11.8%, n =  310/2620), amoxicillin/clavulanic acid (8.8%, n =  231/2620) and ciprofloxacin (7.8%, n =  204/2620). The majority (52.2%; n =  1367/2620) of antibiotics were prescribed to treat an infection, whilst surgical prophylaxis accounted for 26.1% ( n =  684/2620). Conclusions: We observed a high use of antibiotics including metronidazole and cephalosporins at the participating hospitals. Most antibiotics were empirically prescribed, with low use of microbiological cultures. High usage of third-generation cephalosporins especially for community-acquired infections offers an opportunity for antibiotic stewardship interventions.